Surreptitious sympatry: Exploring the ecological and genetic separation of two sibling species. Issue 6 (12th February 2017) - Cordes, Line S.; O'Corry‐Crowe, Gregory; Small, Robert J.
Abstract: Climate change is having profound impacts on animal populations, and shifts in geographic range are predicted in response. Shifts that result in range overlap between previously allopatric congeneric species may have consequences for biodiversity through interspecific competition, hybridization, and genetic introgression. Harbor seals ( Phoca vitulina ) and spotted seals ( Phoca largha ) are parapatric sibling species and areas of co‐occurrence at the edges of their range, such as Bristol Bay, Alaska, offer a unique opportunity to explore ecological separation and discuss potential consequences of increased range overlap resulting from retreating sea ice. Using telemetry and genetic data from 14 harbor seals and six spotted seals, we explored the ecological and genetic separation of the two species by comparing their utilization distributions, distance from haul‐out, dive behavior (e.g., depth, duration, focus), and evidence of hybridization. Firstly, we show that harbor and spotted seals, which cannot be visually distinguished definitively in all cases, haul‐out together side by side in Bristol Bay from late summer to early winter. Secondly, we observed subtle rather than pronounced differences in ranging patterns and dive behavior during this period. Thirdly, most spotted seals in this study remained close to shore in contrast to what is known of the species in more northern areas, and lastly, we did not find any evidence of hybridization. The lack of distinct ecological separation in this area of sympatry suggests that interspecific competition could play an important role in the persistence of these species, particularly if range overlap will increase as a result of climate‐induced range shifts and loss of spotted seal pagophilic breeding habitat. Our results also highlight the added complexities in monitoring these species in areas of suspected overlap, as they cannot easily be distinguished without genetic analysis. Predicted climate‐induced environmental change will likely influence the spatial and temporal extent of overlap in these two sibling species. Ultimately, this may alter the balance between current isolating mechanisms with consequences for species integrity and fitness. Abstract : Climate‐induced range shifts may result in increased geographic overlap between previously allopatric or parapatric species which in turn may have consequences for biodiversity through interspecific competition or genetic introgression in closely related species. Despite showing clearly distinctive ecological differences in areas of allopatry, the temporal, gender, and size‐specific differences in habitat utilization and dive behavior between harbor and spotted seals were often greater than the species‐specific differences in areas of sympatry. The lack of distinct ecological separation between the two species in this area of sympatry suggests that interspecific competition could play an important role in their persistence, particularly as predicted climate‐induced environmental change will likely influence the spatial and temporal extent of overlap in these two sibling species.